Human Monoclonal Antibody Cocktail for the Treatment or Prophylaxis of Middle East Respiratory Syndrome Coronavirus. (28th January 2021) - Sivapalasingam, Sumathi; Saviolakis, George A; Kulcsar, Kirsten; Nakamura, Aya; Conrad, Thomas; Hassanein, Mohamed; Sumner, Giane; Elango, Chinnasamy; Kamal, Mohamed A; Eng, Simon; Kyratsous, Christos A; Musser, Bret J; et al.
Abstract: Background: REGN3048 and REGN3051 are human monoclonal antibodies (mAb) targeting the spike glycoprotein on the Middle East respiratory syndrome coronavirus (MERS-CoV), which binds to the receptor dipeptidyl peptidase-4 (DPP4) and is necessary for infection of susceptible cells. Methods: Preclinical study: REGN3048, REGN3051 and isotype immunoglobulin G (IgG) were administered to humanized DPP4 (huDPP4) mice 1 day prior to and 1 day after infection with MERS-CoV (Jordan strain). Virus titers and lung pathology were assessed. Phase 1 study: healthy adults received the combined mAb (n = 36) or placebo (n = 12) and followed for 121 days. Six dose levels were studied. Strict safety criteria were met prior to dose escalation. Results: Preclinical study: REGN3048 plus REGN3051, prophylactically or therapeutically, was substantially more effective for reducing viral titer, lung inflammation, and pathology in huDPP4 mice compared with control antibodies and to each antibody monotherapy. Phase 1 study: REGN3048 plus REGN3051 was well tolerated with no dose-limiting adverse events, deaths, serious adverse events, or infusion reactions. Each mAb displayed pharmacokinetics expected of human IgG1 antibodies; it was not immunogenic. Conclusions: REGN3048 and REGN3051 in combination were well tolerated. The clinical and preclinical data support further development for the treatment or prophylaxis of MERS-CoV infection. Abstract : REGN3048 and REGN3051 in combination were well tolerated. Each monoclonal antibody displayed pharmacokinetics expected of human IgG1 antibodies; it was not immunogenic. Clinical and preclinical data support further development of REGN3048 and REGN3051 for the treatment or prophylaxis of MERS-CoV infection.